Altered Chemokine Signalling in Endothelial Progenitor Cells from Acute Ulcerative Colitis Patients. (8th February 2015) - De Toni, L.; Di Nisio, A.; Magagna, S.; Michielan, A.; Martinato, M.; Sturniolo, G. C.; D'Incà, R.; Foresta, C.; Garolla, A.
Abstract : Ulcerative colitis (UC) is a chronic, idiopathic, inflammatory bowel disease, characterized by alternating stages of clinically active and inactive disease. UC exhibits several inflammatory characteristics, including immune activation, leukocyte infiltration, and altered vascular density. In UC, many of the upregulated inflammatory cytokines are proangiogenic and are released by diverse cell populations, such as infiltrating immune cells and endothelial cells (EC). Increasing evidences suggest that neovascularisation may involve also endothelial progenitor cells (EPCs). In this study we evaluated EPCs recruitment and homing, assessed by CXCR4 expression, in both acute and remitting phase of UC. We report an overall decrease of EPCs in UC patients (controls = 97, 94 ± 37, 34 cells/mL; acute = 31, 10 ± 25, 38 cells/mL; remitting = 30, 33 ± 19, 02 cells/mL; P < 0.001 for both UC groups versus controls). Moreover CXCR4 + -EPCs, committed to home in inflammatory conditions, were found to be reduced in acute UC patients compared to both remitting patients and controls (acute = 3, 13 ± 4, 61 cells/mL; controls = 20, 12 ± 14, 0; remitting = 19, 47 ± 12, 83; P < 0, 001 ). Interestingly, we found that administration of anti-inflammatory drugs in acute UC is associated with an increase in circulating EPCs, suggesting that this therapy may exert a strong influence on the progenitor cells response to inflammatory processes.